High plasma basic fibroblast growth factor concentration is associated with response to Thalidomide in progressive multiple myeloma - Neben, Kai; Möhler, Thomas; Egerer, Gerlinde; Krämer, Alwin; Hillengaß, Jens; Benner, Axel; Ho, Anthony Dick; Goldschmidt, Hartmut (Clinical cancer research, 2001)
The aim of this study was to define prognostic factors that might be predictive for response to thalidomide (Thal) in progressive multiple myeloma (n = 54). We examined the concentration of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), two potent heparin-binding mediators of angiogenesis in peripheral blood (PB; PB-VEGF and PB-bFGF) and bone marrow (BM; BM-VEGF and BM-bFGF), in combination with well-characterized predictors for response and survival to chemotherapy. After a median follow-up time of 15 months (range, 0.3-20), 29 patients (pts.) showed at least a minimal response to Thal therapy, whereas 25 pts. were nonresponsive. As shown by univariate analysis, responsive pts. had statistically significant higher concentrations of PB-bFGF (P = 0.009) and β2-microglobulin (P = 0.03) before therapy, as well as lower hemoglobin (P = 0.008) and albumin (P = 0.02) levels, whereas no statistically significant difference was found for PB-VEGF (P = 0.93). When a multiple logistic regression analysis was performed, PB-bFGF was the only statistically significant predictor for response to therapy (P = 0.01). None of these variables was associated with a prolonged progression-free survival. In conclusion, our findings indicate that high pretreatment plasma bFGF levels in pts. with progressive multiple myeloma are associated with unfavorable parameters of response and survival but nevertheless predict for response to Thal therapy.